Corticospinal excitability during shortening and lengthening actions with incremental torque output. Issue 12 (16th October 2018) - Škarabot, Jakob; Tallent, Jamie; Goodall, Stuart; Durbaba, Rade; Howatson, Glyn
Abstract : New Findings: What is the central question of this study? The relationship between motor unit recruitment and firing rate has been related to the size of the corticospinal output with variations in the nervous system gain during isometric contractions. However, corticospinal behaviour with incremental torque output might differ during anisometric contractions owing to differences in neural control of anisometric contraction types. What is the main finding and its importance? Corticospinal excitability during lengthening contractions was smaller compared with shortening but increased with incremental torque output in a similar manner between contraction types. The relationship between motor unit recruitment and firing rates is probably the main determinant of the size of an evoked response with variations in system gain. Abstract: The modulation of motor evoked potentials (MEPs), an index of corticospinal excitability, has been shown to increase during isometric contractions with incremental torque output in accordance with the contribution between motor unit recruitment and firing rate of the muscle to increases in required torque output. However, the motor unit strategy of the muscle might not be the only factor influencing this behaviour, because differences in pre‐ and postsynaptic control have been reported between lengthening and shortening or isometric contractions. In 30 healthy adults, MEPs were elicited in tibialis anterior during shortening and lengthening contractions at 15, 25, 50 and 80% of contraction‐type‐specific maximal voluntary contraction torque. Background EMG activity increased progressively with greater torque output ( P < 0.001) but was similar between contraction types ( P = 0.162). When normalized to the maximal muscle response, MEPs were greater during shortening compared with lengthening contractions ( P = 0.004) and increased stepwise with increased contraction intensities ( P = 0.001). These data show an increase in corticospinal excitability with torque output from lower to higher contraction intensities, suggesting a greater contribution of motor unit recruitment to increased nervous system gain in the tibialis anterior. Despite differences in corticospinal control of shortening and lengthening contractions, the data suggest that the corticospinal responses to increases in torque output are not dependent on contraction type, because corticospinal excitability increased to a similar extent during shortening and lengthening actions. Thus, it is likely that the relationship between motor unit recruitment and firing rate of the muscle is the main determinant of corticospinal output with variations in nervous system gain. Abstract :